2020
DOI: 10.1021/acscatal.0c04106
|View full text |Cite
|
Sign up to set email alerts
|

Methanethiol SAMs Induce Reconstruction and Formation of Cu+ on a Cu Catalyst under Electrochemical CO2 Reduction

Abstract: Cu electrode-based electrochemical CO 2 reduction using renewable energy is a promising method for conversion of CO 2 to useful compounds such as methane, ethylene, and ethanol. Heteroatom-doped and/or -derived Cu as oxide-derived Cu has been investigated in context of development of a stable catalyst with high selectivity, whereas the role of heteroatoms is not yet well understood. It is not known whether heteroatoms act as a moiety of the catalyst or simply induce reconstruction of the catalyst. This work is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 67 publications
4
47
0
Order By: Relevance
“…introduced methanethiol monolayers to the Cu electrode to induce the formation of Cu(I) in the electrode. [ 148 ] Lee et al. fabricated Cu 2 O via electrodeposition, and they found that Cu 2 O remains on the surface of catalysts under CO 2 R condition, which is attributed to be the origin of the high selectivity toward CH 4 .…”
Section: Dynamic Changes Of the Cathodic Catalyst During Co2rmentioning
confidence: 99%
See 1 more Smart Citation
“…introduced methanethiol monolayers to the Cu electrode to induce the formation of Cu(I) in the electrode. [ 148 ] Lee et al. fabricated Cu 2 O via electrodeposition, and they found that Cu 2 O remains on the surface of catalysts under CO 2 R condition, which is attributed to be the origin of the high selectivity toward CH 4 .…”
Section: Dynamic Changes Of the Cathodic Catalyst During Co2rmentioning
confidence: 99%
“…[147] Moreover, Masuda et al introduced methanethiol monolayers to the Cu electrode to induce the formation of Cu(I) in the electrode. [148] Lee et al fabricated Cu 2 O via electrodeposition, and they found that Cu 2 O remains on the surface of catalysts under CO 2 R condition, which is attributed to be the origin of the high selectivity toward CH 4 . [58] Overall, it is clear that there is a strong correlation between the existence of Cu(I) species and the high selectivity toward the further reduced product, for example, CH 4 , C 2 H 4 , however, explicit mechanistic understanding behind this effect is still pending.…”
Section: Cu-based Systemsmentioning
confidence: 99%
“…3b). 40,41 The Zr XPS spectra revealed that Zr 4+ was the main Zr species in the ZrO 2 /Cu-Cu 2 O catalyst, which is confirmed by the two peaks at 185.5 eV and 182.9 eV attributed to 3d 3/2 and 3d 5/2 of Zr 4+ , respectively (Fig. 3c).…”
Section: Resultsmentioning
confidence: 69%
“…There are many reported examples having varied molecular structures and ligands extensively used by many scientists in this field. [57,62,63,116,117] For example, cobalt(III) triphenylphosphine corrole (Cocorrole) complex was demonstrated by Gonglach et al. [57] This Co-corrole complex contains three polyethylene glycol residues attached at the meso-phenyl groups.…”
Section: Organometallic Complexmentioning
confidence: 99%
“…Functionalizing metal based electro-catalysts with different surface ligands is an effective way to enhance ECO 2 R performance. Iijima et al [116] reported Cu electrode modified with methanethiol monolayers (MTÀ Cu) for ECO 2 R. The roughened surface and the Cu + moiety, generated due to methanethiol during ECO 2 R, promote C 2 product formation. The Ni II complex with free amine functional group [Ni II L NH2 ] was also reported for ECO 2 R. [62] The Ni II complex produced ethanol with 49 % FE at À 1.60 V (vs. Ag/AgCl).…”
Section: Surface Ligandsmentioning
confidence: 99%